UJI PARAMETER SPESIFIK DAN NON SPESIFIK EKSTRAK ETANOL DAUN SAMBILOTO (Andrograpis Paniculata N.) - Jupita; Astrid Vanessa Putri Erwanda; Dwi Fitrianik; Fahmi Wafiq Khoirunisa; Ramadhani Eka Yoga Maryono; Syafa Auliya Rosyidah (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
ABSTRACT Sambiloto, or Andrographis Paniculata, is one of the plants used as medicine. The active compound andrographolide is found in the bitter plant, which belongs to the Acanthaceae family. With the molecular formula C20H30O5, andrographolide is a compound in the trihydroxylactone group. This research used a bitter extract from 96% ethanol and bitter leaf powder. This research aimed to determine the test results of specific, and non-specific parameters and the secondary metabolite content of ethanol extract from sambioto (Andrographis Paniculata) leaves. In testing specific and non-specific parameters, the results obtained were by the established requirements: organoleptic tests, water-soluble essence content tests, ethanol-soluble essence content tests, and ash content tests. In testing the phytochemistry of the ethanol extract of bitter leaf (Andrographis paniculata), the secondary metabolites contained in the bitter leaf are saponins, polyphenols, tannins, steroids, and terpenoids. Keywords: Sambiloto (Andrographis paniculata), specific parameters, non-specific parameters, phytochemical test